The Many Faces of Primary Aldosteronism and Cushing Syndrome: A Reflection of Adrenocortical Tumor Heterogeneity - Mete, Ozgur; Duan, Kai (Frontiers in Medicine, 2018)
Adrenal cortical tumours constitute a heterogeneous group of neoplasms with distinct clinical, morphological and molecular features. Recent discoveries of specific genotype-phenotype correlations in adrenal cortical adenomas have transformed our understanding of their respective endocrine syndromes. Indeed, a proportion of patients with primary aldosteronism are now known to harbor adrenal cortical adenomas with heterogeneous molecular alterations (KCNJ5, ATP1A1, ATP2B3, CACNA1D) involving the calcium/calmodulin kinase signaling pathway. Several lines of evidence suggest that KCNJ5-mutant aldosterone-producing adenomas have distinct clinicopathological phenotype compared to those harboring ATP1A1, ATP2B3 and CACNA1D mutations. Benign adrenal cortical tumours presenting with Cushing syndrome often have diverse mutations (PRKACA, PRKAR1A, GNAS, PDE11A, PDE8B) involving the cyclic AMP signalling pathway. In addition to cortisol-producing adenomas, bilateral micronodular adrenocortical disease and primary bilateral macronodular hyperplasia (PBMAH) have also expanded the spectrum of benign neoplasms causing adrenal Cushing disease. The recent discovery of inactivating ARMC5 germline mutations in PBMAH has challenged the old belief that this disorder is a mainly a sporadic disease. Emerging evidence suggests that PBMAH harbors multiple distinct clonal proliferations, reflecting the heterogeneous genomic landscape of this disease. Although most solitary adrenal cortical tumours are sporadic, there is increasing recognition that inherited susceptibility syndromes may also play a role in their pathogenesis. This review highlights the molecular and morphological heterogeneity of benign adrenal cortical neoplasms, reflected in the diverse presentations of primary aldosteronism and adrenal Cushing syndrome.